Performance Evaluation of Internal Verifier in Reducing Pending Inpatient Claims of BPJS Kesehatan at Muhammadiyah Hospital North Sumatra 2022 - Amalia Hasibuan; Ermi Girsang; Sri Lestari Ramadhani Nasution (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
This study evaluates the effectiveness of internal verifiers at Muhammadiyah Hospital North Sumatra in minimizing delayed inpatient claims submitted to BPJS Kesehatan, Indonesia's national health insurance agency. A mixed-methods sequential explanatory design was employed, combining quantitative data from 2020 (prior to verifier recruitment) and 2022 (post-recruitment) with qualitative insights from interviews with internal verifiers, coders, and other stakeholders, as well as a review of claim files processed by the hospital's BPJS Unit. Interview protocols were adapted from a 2018 study at Koja Hospital, North Jakarta, and data were analyzed using the Miles and Huberman approach, with findings integrated across methods. Source triangulation ensured validity and reliability. Results showed that internal verifiers significantly reduced the proportion of delayed claims despite an overall increase in submissions, with the highest rate of pending claims dropping from 25.6% in 2020 to 17.9% in 2022. Of the 2022 delays, 31.2% were due to BPJS Kesehatan system errors or confirmation processes, indicating that only two-thirds stemmed from hospital-related issues. Qualitative analysis identified key contributors to delays, including diagnostic coding errors, inconsistent understanding among BPJS verifiers, incomplete documentation, limited staff knowledge, and human resource inaccuracies. The presence of internal verifiers improved claim management and hospital revenue by increasing eligibility and accelerating approvals. To further optimize claim processing, strategies such as enhancing coding accuracy, improving staff competency, ensuring documentation completeness, and adopting electronic systems with supportive incentives are recommended. Keyword: Internal verifier, pending claims, performance